Psidium guajava: A Single Plant for Multiple Health Problems of Rural Indian Population - Daswani, Poonam G.; Gholkar, Manasi S.; Birdi, Tannaz J. (Pharmacognosy Reviews)
The rural population in India faces a number of health problems and often has to rely on local remedies. Psidium guajava Linn. (guava), a tropical plant which is used as food and medicine can be used by rural communities due to its several medicinal properties. A literature search was undertaken to gauge the rural health scenario in India and compile the available literature on guava so as to reflect its usage in the treatment of multiple health conditions prevalent in rural communities. Towards this, electronic databases such as Pubmed, Science Direct, google scholar were scanned. Information on clinical trials on guava was obtained from Cochrane Central Register of Controlled Trials and Clinicaltrial.gov. The literature survey revealed that guava possesses various medicinal properties which have been reported from across the globe in the form of ethnobotanical/ethnopharmacological surveys, laboratory investigations and clinical trials. Besides documenting the safety of guava, the available literature shows that guava is efficacious against the following conditions which rural communities would encounter. (a) Gastrointestinal infections; (b) Malaria; (c)Respiratory infections; (d) Oral/dental infections; (e) Skin infections; (f) Diabetes; (g) Cardiovascular/hypertension; (h) Cancer; (i) Malnutrition; (j) Women problems; (k) Pain; (l) Fever; (m) Liver problems; (n) Kidney problems. In addition, guava can also be useful for treatment of animals and explored for its commercial applications. In conclusion, popularization of guava, can have multiple applications for rural communities.
Keywords: Guava; India; Psidium guajava; review; rural communities